Pendidikan Akhlak Siswa di Era Digitalisasi - Indah Nola; Mukhbita Alya; Rika Mutiara Shandi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This article explores the moral dimensions of students from an Islamic perspective amid the challenges of globalization and digitalization. The focus is on analyzing the moral values contained in Surah Ali-Imran verses 13, 14, 18, and 19, which emphasize the importance of faith, steadfastness, acknowledgment of the truth of monotheism, and the significance of Islam as a way of life. The digital era has transformed students' mindsets and behaviors, potentially weakening their moral values. Therefore, moral education based on the Qur'an serves as a strategic solution to strengthen students' character by integrating spiritual, moral, and social values into the learning process. This article also proposes a holistic approach that utilizes technology while remaining grounded in Islamic principles, aiming to shape a generation with noble character in the midst of modernization.